A six‐year review of more than 13, 000 patient‐specific IMRT QA results from 13 different treatment sites. (8th September 2014) - Pulliam, Kiley B.; Followill, David; Court, Laurence; Dong, Lei; Gillin, Michael; Prado, Karl; Kry, Stephen F.
Abstract : Due to a lack of information regarding the current clinical experience of IMRT QA for a large and varied plan population, we reviewed our patient‐specific IMRT quality assurance (QA) results for 13, 003 treatment plans from 13 distinct treatment sites from a six‐year period. QA records were reviewed for dose difference (single point with ion chamber measurement; ± 3 % agreement criteria) and percentage of pixels passing relative dose gamma analysis (film measurement; 90% passing 5%(global)/3 mm agreement criteria) from 2005 through 2011. Plan records were analyzed for trends with measurement date and treatment site. Plans failing to meet QA tolerance criteria were evaluated for follow‐up clinical action (i.e., if repeat measurements were performed). The mean difference ( ± SD ) between ion chamber point measurements and calculated doses was ‐ 0.29 % ± 1.64 % (calculated values being slightly higher) and, regarding planar dose evaluations, the mean percentage of pixels passing the gamma criteria of 5%(global)/3 mm was 97.7% (lower 95th percentile: 92.2%). 97.7% and 99.3% of plans passed the point dose and planar dose verification, respectively. We observed statistically significant differences ( p < 0.05 ) in both point dose and planar dose verification measurements as a function of treatment site (particularly for stereotactic spine and mesothelioma sites) and measurement date (average agreement improved with time). However, despite improved dosimetric agreement, the percentage of failing plans has remained nearly constant at 2.3%. PACS numbers: 87.55.Qr, 87.55.km, 87.56.Fc